Market Share Bank Syariah Terhadap Institusi Keuangan Syariah di Indonesia: (The Market Share of Islamic Banks to Islamic Financial Institution in Indonesia) - Moh. Adenan; Ghaluh Hermawati Safitri; Lilis Yuliati (UPT Penerbitan Universitas Jember, 2021)
Sharia banking is a sharia financial institution that is considered to have contributed to the national economy. Judging from the value of the market share owned by Islamic banking, it is still relatively low compared to Malaysia. This study aims to determine the effect of Islamic capital market products and Islamic banking on the market share of Islamic banking assets in Indonesia. The Islamic capital market products used are in the form of Islamic stocks, corporate sukuk and Islamic mutual funds. Meanwhile, in Islamic banking, there are Islamic demand deposits, Islamic savings and Islamic deposits. Empirically the focus of this research is using monthly time series data from January 2014 to December 2019. This study uses the Vector Error Correction Model (VECM) analysis method. The estimation results of this study indicate that in the long term, corporate sukuk, sharia demand deposits and Islamic savings have a positive and significant effect on the market share of Islamic banking assets in Indonesia. Meanwhile, Islamic mutual funds and Islamic deposits have a negative and significant effect. Meanwhile, Islamic stocks have a negative and insignificant effect on the market share of Islamic banking assets in Indonesia. On the other hand, in the short term only Islamic deposits have a positive and significant effect. Corporate sukuk has a positive and insignificant effect, while Islamic stocks, Islamic mutual funds, Islamic demand deposits and Islamic savings have a negative and insignificant effect on the market share of Islamic banking assets in Indonesia.